2014
DOI: 10.3945/jn.113.185009
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing a Low-Protein Diet with Dibasic Amino Acids Increases Urinary Calcium Excretion in Young Women

Abstract: Increasing dietary protein within a physiologic range stimulates intestinal calcium absorption, but it is not known if specific amino acids or dietary protein as a whole are responsible for this effect. Therefore, we selectively supplemented a lowprotein (0.7 g/kg) diet with either the calcium-sensing receptor-activating amino acids (CaSR-AAAs) L-tryptophan, L-phenylalanine, and L-histidine, or the dibasic amino acids (DAAs) L-arginine and L-lysine, to achieve intakes comparable to the content of a high-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Both GH and IGF-I are osteogenic with some of the effects of GH mediated via IGF-I ( Yakar et al, 2002 ; Locatelli and Bianchi, 2014 ; Ohlsson et al, 1998 ). In addition, the relatively high levels of arginine and lysine compared to animal-based proteins, might increase calcium absorption ( Bihuniak et al, 2014 ). Soy protein increases expression of intestinal calcium transporters, specifically TRPV6, in rats ( Gaffney-Stomberg et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both GH and IGF-I are osteogenic with some of the effects of GH mediated via IGF-I ( Yakar et al, 2002 ; Locatelli and Bianchi, 2014 ; Ohlsson et al, 1998 ). In addition, the relatively high levels of arginine and lysine compared to animal-based proteins, might increase calcium absorption ( Bihuniak et al, 2014 ). Soy protein increases expression of intestinal calcium transporters, specifically TRPV6, in rats ( Gaffney-Stomberg et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, studies from Wasserman and colleagues reported an effect of lysine and arginine on calcium absorption in rats (Comar et al, 1956; Wasserman et al, 1957). We also recently demonstrated a trend toward higher calcium absorption in young women when a low-protein diet was supplemented with arginine and lysine (Bihuniak et al, 2014). The data from Torricelli et al (2002, 2003) underscore the importance of a comprehensive analysis of the effects of amino acids on bone cells both individually as well as in functionally relevant combinations.…”
Section: The Effect Of Dietary Protein On Adult Skeletal Healthmentioning
confidence: 99%
“…The authors hypothesized that L-lysine and vitamin D may be acting via different cellular pathways to increase intestinal calcium absorption. We recently undertook a crossover feeding study in 14 young Asian and Caucasian women and assessed the effect of amino acid supplementation on intestinal calcium absorption (Bihuniak et al, 2014). Each participant ingested a low-protein diet (0.7 g protein/kg) supplemented with: (1) L-tryptophan, L-phenylalanine, and L-histidine, (2) L-arginine and L-lysine, and (3) methylcellulose capsules (control) and calcium absorption was assessed after 6 days using dual stable calcium isotopes.…”
Section: The Effect Of Dietary Protein On Adult Skeletal Healthmentioning
confidence: 99%
“…Animal proteins raise the renal acid load, which is associated with reduced excretion of lithogenesis inhibitors such as citrate [72,73] and incident kidney stones in population-based studies [74]. Amino acid and protein supplementation are also associated with increased urinary calcium excretion [75,76], while mild protein intake restriction reduces calcium excretion [77]. Thus, limiting animal protein intake is one of the cornerstone measures for preventing calcium lithiasis recurrence [16,17,62].…”
Section: Animal Proteins and Microbiotamentioning
confidence: 99%